The Spatiotemporal Dynamics and Microevolution Events That Favored the Success of the Highly Clonal Multidrug-Resistant Monophasic Salmonella Typhimurium Circulating in Europe - Cadel-Six, Sabrina; Cherchame, Emeline; Douarre, Pierre-Emmanuel; Tang, Yue; Felten, Arnaud; Barbet, Pauline; Litrup, Eva; Banerji, Sangeeta; Simon, Sandra; Pasquali, Federique; Gourmelon, Michèle; Mensah, Nana; et al. (Frontiers in Microbiology, 2021)
The monophasic variant of Typhimurium (S. 1,4,[5],12:i:-) is the most frequently isolated serovar in the agro-food sector and humans in Europe, the US and several regions of the world. In order to better understand the genomic diversity of this serovar in Europe, we undertook the phylogenetic analysis of 289 S. Typhimurium and monophasic Typhimurium genomes isolated over eighteen years from animal, food, feed, environment and humans from five countries, Denmark, France, Germany, Italy and the UK. Even though 12 genomic lineages of S. 1,4,[5],12:i:- were identified, the lineage corresponding to epidemic clone, characterized by the multi locus sequence type ST34, included 90 % of the strains confirming the evolutionary success of this highly pathogenic clone. The analysis of the core and accessory genome allowed us to show that this clone possesses, as heritage of the Typhimurium from which it rise, the SodCl factor enabling it to survive in the host macrophages, bcfA and cgsD genes to form biofilms to persist in the environment. Bayesian analysis of the genomes belonging to the epidemic clone ST34 lineage made it possible to date its appearance in Europe and each of the genomic modifications that marked its evolutionary success. The integration in the 1980s of the Tn21 transposon into the fljAB locus and the acquisition of the Salmonella Genomic Island (SGI)-4 at the 3' end of the phenylalanine phe tRNA locus have conferred resistance to mercury toxicity and several classes of antibiotics used in food-producing animals. Subsequently, the numerous exchanges of mobile genetic material with other Enterobacteria that colonise the intestinal lumen of farm animals enabled it to acquire in the 1990s resistance to copper and arsenic, the ability to reduce nitrates in intestinal contents and facilitate the disruption of the junctions of the host intestinal epithelial cells. The genomic plasticity of the epidemic monophasic Typhimurium was demonstrated in our study by the analysis of the plasmidome. We were able to identify plasmids harboring genes mediating for phenicols, colistin and fluoroquinolone resistance. We also described for the first time two plasmids previously described only in strains of enterotoxigenic E. coli and E. fergusonii.